Alphakids: finding rainbow - Nagle, Shane (Eleanor Curtain Pub. Prahran, Vic., 2004)
"Finding Rainbow" could be a beautiful story about a quest for something special or a metaphorical journey. Maybe it follows a character searching for a lost friend, a dream, or even the colorful joys of life. Would you like to dive deeper into this theme? We could brainstorm plot ideas or explore character development!